Nanocomposite polymer gel electrolyte based on LiBOB-cellulose acetate for Lithium-Oxygen Battery / Siti Zafirah Zainal Abidin - Zainal Abidin, Siti Zafirah (2016)
This thesis focuses on the preparation and characterization of liquid electrolytes (LEs), polymer gel electrolytes (PGEs) and nanocomposite polymer gel electrolytes (NCPGEs). In this work, lithium bis(oxalato) borate (LiBOB) salt was incorporated as the source of charge carriers. LEs were first prepared by dissolving LiBOB in the solvent, y-butyrolactone using various molar concentrations of LiBOB. The optimum conductivity (0.8 M LiBOB) of the liquid electrolyte was then gelled with different concentrations of cellulose acetate (CA) to form PGEs. The ionic conductivity of all electrolyte samples were calculated using the bulk resistance value obtained from the complex impedance plot in the frequency range between 100 Hz to 1 MHz. The ionic conductivity pattern of PGEs slightly increases at low cellulose acetate concentration and starts declining with increasing cellulose acetate content. The conductivity reaches a maximum value of 7.05 mS cm'1 for the electrolyte containing 2.4 wt.% CA at room temperature. This phenomenon is best clarified by the Breathing Polymeric Chain model. Although PGE has a high conductivity, its physical properties and dimensional stability need to be improved for practical application. Therefore, the highest conductivity of PGE was dispersed with different weight ratios of nanosized silica to obtain NCPGEs. The highest conductivity of 6.49 mS cm-1 is obtained with the addition of 2.5 wt.% Si02. Ionic conductivity for all systems was also studied as a function of temperature from 303 K up to 363 K. The plot of log o versus 1000/T for each sample obeys Arrhenius rule implying the ionic conductivity to be thermally assisted. The conduction mechanism in liquid electrolyte, polymer gel electrolyte and nanocomposite polymer gel electrolyte can be best explained using the small polaron hopping (SPH) model since the power law exponent s increases with the increase in temperature. Transference number characterization supports the ionic conductivity results. The voltammogram of highest conducting NCPGE with an anodic decomposition limit of the electrolyte was stable up to 5.5 V vs. Li. The addition of nanosized silica into PGE enhances the physical properties which is supported by the results of viscosity and Enviromental Scanning Electron Microscope (ESEM). Fourier Transform Infrared (FTIR) spectroscopy was performed to study the molecular interaction between components in each electrolyte system. The complexations between the materials used in electrolyte systems are divulged based on shifting of the bands, changes in intensity of the bands, changes in shape and existence of some new peaks in FTIR spectra. The highest conducting PGE and NCPGE were chosen as an electrolyte to fabricate Lithium-Oxygen battery. Lithium-Oxygen battery containing nanocomposite polymer gel electrolytes exhibits the most stable performance with higher discharge time and discharge capacity. The formation of discharge products (i.e. Li202 and Li20) are also reduced since the nanosized silica particles enforcing their formation in only nanosize during discharge appear on the carbon air-electrode.